Application of Theory of Planned Behavior to counterfeit garment brands purchase: a qualitative research (International Journal of Scientific Research and Management (IJSRM), 2014)
Theory of Planned Behavior has been used in a number of studies to understand the consumer behavior. Almost all such researches have utilized quantitative methods for research. In this research, an attempt has been made to apply the Theory of Planned Behavior to the counterfeit garment brand purchase using qualitative methods. This research tried to identify the factors that influence consumers to buy or not to buy counterfeit garment brands based on the constructs of Theory of Planned Behavior. Three focus group interviews were conducted for 30 people in a group of ten each. The three groups comprised of respondents from different age groups. The responses were hence analyzed to identify the similarities and differences in the factors of importance while purchasing branded/ counterfeit garments between the three groups of respondents